Processes of qualification to the secular clergy of Mariana (1745-1764) - Faria Duarte, Josimar (2021)
The study on screen deals with the qualification processes for the secular clergy de Mariana, during the episcopal government of frei Manuel da Cruz (1745-1764). The research instrument consisted of using the prosopographic method, proposed by regional history. The empirical sources of support used were handwritten documents consulted in the Ecclesiastical Archive of the Archdiocese of Mariana. The conceptual theoretical apparatus refers to the recent historiography on empire, networks, connections and relations between center and periphery, central power and local power. The results of this research are presented here from modal narratives.